2013
DOI: 10.1186/2193-1801-2-457
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the muscle strength by the muscle thickness and hardness using ultrasound muscle hardness meter

Abstract: PurposesThe present study investigated whether a combination of the thickness and hardness of muscles without muscle tension can be used to estimate muscle strength during knee extension in adult males and females.MethodsSeventy-two males and thirty-three females, whose ages ranged from 18 to 35 years, participated in this study. We measured muscle thickness and hardness in the right anterior region of the thigh (rectus femoris muscle and vastus intermedius muscle) without muscle tension using an ultrasound mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 32 publications
(43 reference statements)
0
18
1
Order By: Relevance
“…There are several possible explanations for this discrepancy; anisotropic properties in the human skeletal muscle may be a cause in addition to the differences in modulus and devices used for the measurements. 18,[22][23][24] With the use of the MRE, the shear moduli measured in the direction parallel to the muscle fibre were greater than those measured in the direction perpendicular to the fibre, whereas the values themselves were very different from those reported in earlier studies. 25 In the present study, therefore, we did not express the masseter muscle elasticity in kilopascal using the Young's moduli because the aim of present study was to verify the correlation between the EI ratios and the elasticity of the muscle phantoms.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…There are several possible explanations for this discrepancy; anisotropic properties in the human skeletal muscle may be a cause in addition to the differences in modulus and devices used for the measurements. 18,[22][23][24] With the use of the MRE, the shear moduli measured in the direction parallel to the muscle fibre were greater than those measured in the direction perpendicular to the fibre, whereas the values themselves were very different from those reported in earlier studies. 25 In the present study, therefore, we did not express the masseter muscle elasticity in kilopascal using the Young's moduli because the aim of present study was to verify the correlation between the EI ratios and the elasticity of the muscle phantoms.…”
Section: Discussioncontrasting
confidence: 51%
“…Although the ROIs were set roughly just below the reference coupling agent with the same size in all measurements based on the preliminary test, it may be necessary to determine the location and size strictly as factors affecting the reliability of EI ratio. 17,18 The elasticity of the reference coupling agent was observed to vary over time because Figure 4 The relationship between the elasticity index (EI) ratio and the Young's modulus of the muscle phantom. of dehydration of its material.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses were performed using SPSS Statistics V.23 (IBM Inc, Chicago, IL). The reliability of the measured values of the muscle thickness and torque between the 1st and 2nd measurements were examined by the intraclass correlation coefficient (ICC) (1,2) and (1…”
Section: Discussionmentioning
confidence: 99%
“…Muscle strength is needed for physical activity. Since the test of muscle strength needs a person's maximum exertion, the objective assessment of muscle size is often measured in sedentary people (1). Muscle volume which, is related to muscle cross-sectional area and thickness, is associated with muscle strength (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that MMEI was not cor- The present study showed that MMT was not correlated with MMD and MBF. Muscle thickness is an indicator of muscle strength, 28 and it has been reported to correlate with MBF. 14,15 However, the subjects of these studies were young dentate adults, rather than elderly subjects with tooth loss.…”
Section: Con Clus Ionmentioning
confidence: 99%